2014
DOI: 10.1103/physrevlett.113.016801
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Anomalous Hall Insulator of Composite Fermions

Abstract: We show that a weak hexagonal periodic potential could transform a two-dimensional electron gas with an even-denominator magnetic filling factor to a quantum anomalous Hall insulator of composite fermions, giving rise to fractionally quantized Hall effect. The system provides a realization of the Haldane honeycomb-net model, albeit in a composite fermion system. We further propose a trial wave function for the state, and numerically evaluate its relative stability against the competing Hofstadter state. Possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…We note that our result is modified by the exchange correlation energy of composite fermions (through the parameter a); in contrast, Ref. 37 does not include the exchange correlation energy. Also, the large change in ∆ν (note |∆ν| > 0.5 is not physically acceptable) suggests that the potential is not weak.…”
Section: Additional Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We note that our result is modified by the exchange correlation energy of composite fermions (through the parameter a); in contrast, Ref. 37 does not include the exchange correlation energy. Also, the large change in ∆ν (note |∆ν| > 0.5 is not physically acceptable) suggests that the potential is not weak.…”
Section: Additional Resultsmentioning
confidence: 88%
“…This is not surprising because, as stressed by Karlhede et al 32 , the energetics of spin textures at the edge is closely related to that of skyrmions 34 , and calculations have shown that skyrmions at 1/3 become viable only at very low Zeeman energies 35 . We note that the ChernSimons mean field theory of composite fermions 7,36 has also been used to treat the effect of an external periodic potential on the state in the vicinity of half filling 37,38 ; see SM for a comparison with our approach.…”
Section: (B) and (C) And S2mentioning
confidence: 99%
“…It is the so-called quantum anomalous Hall (QAH) effect, also known as Chern insulators. QAH systems have been intensively studied for their fruitful physics and promising applications in future technology [1][2][3][4][5][6][7][8][9][10][11][12]. They attract the attention of researchers because of the topologically nontrivial chiral edge states in the absence of external magnetic field, which is important to the development of next-generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid struc-tures such as TI/superconductor junctions have been fabricated [39,40], which are expected to give rise to topological superconductivity and Majorana fermions [41,42]. Transport experiments and theoretical work have mostly focused on longitudinal [43][44][45][46][47][48] and Hall transport properties [37,[49][50][51], thermoelectric response [52][53][54] and weak antilocalization [55][56][57][58], all essentially single-particle phenomena. The interplay of strong spin-orbit coupling and electron-electron interactions in TIs is at present not completely understood [59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%